Enhancing Mahārah Kalām: A Comparative Study of Southeast Asian Islamic Universities - Muhajir, Muhajir; Novita Maula Salsabila; Achmad Yani (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2026)
This comparative study explored the implementation of Mahārah Kalām (Arabic speaking skills) at UIN Sunan Kalijaga, Indonesia, and Sultan Sharif Ali Islamic University (UNISSA), Brunei Darussalam, focusing on learning strategies, language environments, and contextual factors influencing language acquisition. A qualitative approach was employed, including document analysis, classroom observations, and semi-structured interviews with lecturers and students. The findings revealed that both institutions prioritized communicative competence through interaction with native speakers and the implementation of bi’ah lughawiyah. UIN Sunan Kalijaga applied bi’ah lughawiyah, project-based learning, and student activity units to mitigate first language interference, while UNISSA integrated bi’ah lughawiyah, cultural activities, Arabic language camps, and direct engagement with native speakers. Despite differences in pedagogical approaches and assessment systems, both universities effectively enhanced students’ confidence, motivation, and speaking proficiency. The study underscored the importance of immersive and culturally responsive learning environments in Arabic language education, offering insights for designing effective curricula to improve students’ oral communication skills across diverse sociolinguistic contexts.